2020
DOI: 10.1080/15548627.2020.1824694
|View full text |Cite
|
Sign up to set email alerts
|

SMAD3 promotes autophagy dysregulation by triggering lysosome depletion in tubular epithelial cells in diabetic nephropathy

Abstract: Macroautophagy/autophagy dysregulation has been noted in diabetic nephropathy; however, the regulatory mechanisms controlling this process remain unclear. In this study, we showed that SMAD3 (SMAD family member 3), the key effector of TGFB (transforming growth factor beta)-SMAD signaling, induces lysosome depletion via the inhibition of TFEB-dependent lysosome biogenesis. The pharmacological inhibition or genetic deletion of SMAD3 restored lysosome biogenesis activity by alleviating the suppression of TFEB, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 63 publications
2
62
0
Order By: Relevance
“…Theodomir et al confirmed that P2Y2R deficiency increased the expression of sirtuin-1 and FOXO3a, which enhanced autophagy and improved renal insufficiency in DKD (95). In addition, Yang et al found that Smad3, the downstream transcription factor activated by TGFβ (transforming growth factor β), suppressed lysosome biogenesis in a TFEB-dependent manner (96). Furthermore, ATF4 (activating transcription factor 4) (97), TRAIL (TNF related apoptosis inducing ligand) (98), Soluble epoxide hydrolase (sEH) and lys63 UB proteins were also confirmed to be involved in the regulation of autophagy in the kidney cells.…”
Section: Autophagymentioning
confidence: 96%
“…Theodomir et al confirmed that P2Y2R deficiency increased the expression of sirtuin-1 and FOXO3a, which enhanced autophagy and improved renal insufficiency in DKD (95). In addition, Yang et al found that Smad3, the downstream transcription factor activated by TGFβ (transforming growth factor β), suppressed lysosome biogenesis in a TFEB-dependent manner (96). Furthermore, ATF4 (activating transcription factor 4) (97), TRAIL (TNF related apoptosis inducing ligand) (98), Soluble epoxide hydrolase (sEH) and lys63 UB proteins were also confirmed to be involved in the regulation of autophagy in the kidney cells.…”
Section: Autophagymentioning
confidence: 96%
“…Human proximal tubular HK‐2 cells (ATCC, CRL‐2190™, Manassas, VA, USA) and mouse renal tubular epithelial cells (mTECs, a gift from Dr Jeffrey B. Kopp, NIH, Bethesda, MD, USA) were cultured as previously described 23 . To mimic CsA‐induced nephrotoxicity in vitro, the cells were treated with 5, 7.5 and 10 μmol/L CsA (Selleck, S2286) for 24 h or an equal amount of ethyl alcohol in the control group.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis was performed as previously described 23 . The membranes were incubated at 4°C overnight with the following primary antibodies: anti‐collagen I (Abcam, ab34710), anti‐TGF‐β1 (Abcam, ab92486), anti‐fibronectin (Abcam, ab23750), anti‐LC3B (Sigma, L7543), anti‐p62/SQSTM1 (Abcam, ab91526), anti‐Cathepsin B (Abcam, ab58802), anti‐phospho‐mTOR (Ser2448) (Cell Signaling, 5536S), anti‐mTOR (Cell Signaling, 2983S), anti‐phospho‐4E‐BP1(Thr37/46) (Cell Signaling, 2855S), anti‐4E‐BP1 (Cell Signaling, 9644S), anti‐phospho‐TFEB (Ser142) (Millipore, ABE1971‐I), anti‐TFEB (BETHYL, A303‐672).…”
Section: Methodsmentioning
confidence: 99%
“…TGF-β/SMAD signaling pathway plays a criticial role in diabetic kidney injuries ( Chen et al, 2011 , 2014a ; Liu et al, 2011 ; Lan, 2012 ; Zhong et al, 2013 ; Li et al, 2014 ; Zhang et al, 2019b ; Xu et al, 2020a ; Yang et al, 2020 ). In the diabetic kidney, high glucose and AGEs enhance the phosphorylation of SMAD3 and decrease the phosphorylation SMAD7.…”
Section: Inflammation In the Progression Of Dnmentioning
confidence: 99%
“…SMAD3 deficiency protects against diabetes-associated beta cell dysfunction and loss in DN mice ( Sheng et al, 2021 ). SMAD3 also promotes autophagy dysregulation and kidney injury ( Yang et al, 2020 ). SMAD7 inhibits IκBα, an NF-κB inhibitor, suppressing the activation of NF-κB pathway ( Chung et al, 2009 ).…”
Section: Inflammation In the Progression Of Dnmentioning
confidence: 99%